LE DÉFI DE COMPLÉMENTARITÉ DE LA CATÉCHÈSE PAROISSIALE ET DE L’ENSEIGNEMENT RELIGIEUX EN POLOGNE - Skłodowski, Bogdan (Studia Katechetyczne, 2016)
The article shows, in detail, the interrelation which occurs between the parish religious education and school teaching of religion in Poland. The author takes up a reflection 25 years after bringing religion back to schools. Starting from establishments of religious education documents of the Catholic and Polish Church, he points at the complementarity of these two forms of the religious education service of the word. It is also related to the possibility of carrying three functions of religious education out - the teaching, the upbringing and acquainting both in the parish, and at the school. In conclusion, the author formulates conclusions which are a response to the complementarity challenge of the parish catechesis and religious education in Poland. In the special way he stresses out the substantial role of liturgy and its connections with the religious education.